THE IMPACT OF COLD WAR ON MIDDLE EAST - Shahkar Mehdi; Ovais Vohra; Fathi F Elsied Elfaghri; Muntazir Mehdi; Saleem Arshad Chheena (International Journal of Contemporary Issues in Social Sciences, 2024)
This research article aims at discussing the various ways in and extents to which the Cold War shaped Middle Eastern geopolitical, societal, and cultural contexts. The Cold War indeed shaped political relations, market development, and sociocultural transformations by setting the America and the Union of socialist Republics against each other. This research focuses on examining the impact of these superpowers and their roles as mediators, direct interference, and strategic partners on the Middle Eastern nations. This article provides a good understanding of the Cold War and how it influenced the Middle East using information from history, such a geo-political shifts and the effects they had on the region, even up to this present time.